Genotypic and bioinformatic evaluation of the alpha-l-iduronidase gene and protein in patients with mucopolysaccharidosis type I from Colombia, Ecuador and Peru - Tatiana Pineda; Sulie Marie; Janneth Gonzalez; Ana L. García; Amparo Acosta; Manuel Morales; Luz N. Correa; Ricardo Vivas; Xiomara Escobar; Ana Protzel; Maria Barba; Sandra Ospina; et al. (Molecular Genetics and Metabolism Reports, 2014)
Mucopolysaccharidosis type I (MPSI) is a rare autosomal recessive disorder caused by mutations in the gene encoding the lysosomal enzyme α-l-iduronidase (IDUA), which is instrumental in the hydrolysis of the glycosaminoglycans, dermatan and heparan sulfate. The accumulation of unhydrolyzed glycosaminoglycans leads to pathogenesis in multiple tissue types, especially those of skeletal, nervous, respiratory, cardiovascular, and gastrointestinal origin. Although molecular diagnostic tools for MPSI have been available since the identification and characterization of the IDUA gene in 1992, Colombia, Ecuador, and Peru have lacked such methodologies. Therefore, the mutational profile of the IDUA gene in these countries has largely been unknown. The goal of this study was to characterize genotypes in 14 patients with MPSI from Colombia, Ecuador, and Peru. The most common mutation found at a frequency of 42.8% was W402X. Six patients presented with seven novel mutations, a high novel mutational rate in this population (32%). These novel mutations were validated using bioinformatic techniques. A model of the IDUA protein resulting from three of the novel missense mutations (Y625C, P385L, R621L) revealed that these mutations alter accessible surface area values, thereby reducing the accessibility of the enzyme to its substrates. This is the first characterization of the mutational profile of the IDUA gene in patients with MPSI in Colombia, Ecuador, and Peru. The findings contribute to our understanding of IDUA gene expression and IDUA enzyme function, and may help facilitate early and improved diagnosis and management for patients with MPSI.